Предмет: Алгебра,
автор: baryshandr
11x^2y-5x+11xy^2-5y ПОМОГИТЕ!!!
Ответы
Автор ответа:
0
11х²у+11ху²-5(х+у)=11ху(х+у)-5(х+у)=(х+у)(11ху-5)
Автор ответа:
0
В итоге (x + y)^2
Автор ответа:
0
11x^2y - 5x + 11xy^2 - 5y =
= x (11xy - 5) + y (11xy - 5) =
= (x + y) (11xy - 5)^2
= x (11xy - 5) + y (11xy - 5) =
= (x + y) (11xy - 5)^2
Автор ответа:
0
^2 а это лишнее)
Автор ответа:
0
Почему лишнее то?
Похожие вопросы
Предмет: Физика,
автор: karinastrelkova14
Предмет: Русский язык,
автор: 291207ayi
Предмет: Литература,
автор: Аноним
Предмет: Математика,
автор: гульнара121212